A comparison of extreme precipitation event frequency and magnitude using a high‐resolution rain gage network and NOAA Atlas 14 across Delaware. (28th December 2019) - Leathers, Daniel J.; Brasher, Saber E.; Brinson, Kevin R.; Hughes, Christopher; Weiskopf, Sam
Abstract: Extreme precipitation events are arguably one of the most important natural hazards in many areas of the globe, impacting nearly every societal sector. In the Northeastern United States, extreme precipitation events have been shown to be increasing with several recent events garnering national attention (i.e., Ellicott City Maryland 2018; Tropical Storm Lee 2011). The NOAA Atlas 14 product is the nation's standard for estimating the magnitude and frequency of site‐specific extreme precipitation events, containing both precipitation frequency estimates, as well as associated confidence intervals. The Atlas uses surface stations, primarily from the National Weather Service Cooperative Observer Program, and statistical methodologies to provide point‐based precipitation exceedance probability estimates for several durations and potential recurrence intervals. Unfortunately, the number and quality of Cooperative Observer sites varies greatly over space and time. This research compares observed precipitation extremes from a high‐resolution statewide mesonet to those estimated by the Atlas 14 product for a 10‐year recurrence interval at several precipitation durations. Results of the analysis indicate that Atlas 14 underestimates the number and magnitude of extreme precipitation events across the state of Delaware at longer event durations (360‐ to 1, 440‐min). At shorter durations (5‐ to 240‐min) the Atlas 14 estimates are more closely aligned with the observations from the high‐resolution precipitation network. These results suggest that caution should be exercised when using Atlas 14 estimates for engineering standards and hydrologic studies, especially for longer duration events. Therefore, a more rapid update cycle for revision of the Atlas 14 product should be considered, as a changing climate regime may be responsible for the differences identified in this research. Abstract : Precipitation values exceeding those estimated for 10‐year recurrence intervals by the NOAA Atlas 14 were identified for each station in the high‐resolution mesonet. Seven stations had two event exceedances, eight stations recorded three event exceedances and six stations recorded four events greater in magnitude than that estimated by Atlas 14 for a 1, 440‐min duration, 10‐year return interval. The probability of four exceedance events in a 10‐year period from random chance is 1.5%.